A comparative review on the anti-nutritional factors of herbal tea concoctions and their reduction strategies - Pathaw, Neeta; Devi, Konjengbam Sarda; Sapam, Redina; Sanasam, Jyotsana; Monteshori, Sapam; Phurailatpam, Sumitra; Devi, Huirem Chandrajini; Chanu, Wangkhem Tampakleima; Wangkhem, Baby; Mangang, Naorem Loya (Frontiers in Nutrition, 2022)
Tea is an important beverage consumed worldwide. Of the different types of tea available, herbal tea is an important beverage consumed owing to its popularity as a drink and stress relieving factors, a number of different herbal concoctions made from seeds, leaves or roots are currently consumed and sold as herbal teas. The herbal teas are not the usual tea but ‘tisanes’. They are caffeine free and popular for their medicinal property or immune boosters. Herbal tea formulations are popularly sold and consumed by millions owing to its health benefits as they are rich in antioxidants and minerals. However, plants are also known to contain toxic and anti-nutritional factors as well. Anti-nutritional factors are known to interfere with the metabolic process and hamper absorption of important nutrients in the body. These anti-nutritional factors include saponins, tannins, alkaloids, oxalates, lectins, goitrogens, cyanogens, and lethogens. These chemicals are known to have deleterious effects on human health. Therefore, it is important to understand and assess the merits and demerits before consumption. Also, several techniques are currently used to process and reduce the anti-nutrients in foods. This review is focused on comparing the contents of various anti-nutritional factors in some underutilized plants of North-East India used as herbal tea along with processing methods that can be used to reduce the level of these anti-nutrients.